Template requirements for initiation of phage phi 29 DNA replication in vitro. - García, J A (1984)
The template requirements for the formation of the phi 29 protein p3-dAMP initiation complex in vitro have been studied. The initiation reaction requires the parental protein p3 but not an intact DNA molecule. Protein p3-containing fragments from the left- or right-hand DNA ends were active as template for formation of the initiation complex provided they had a minimal size: a 26-base-pair-long fragment was active whereas a 10-base-pair-long one was essentially inactive. However, the activity of the latter was restored by ligation of an unspecific DNA sequence. phi 29 DNA internal fragments, as well as denatured phi 29 DNA, were inactive as template for the initiation reaction. The terminal protein-DNA complex isolated from Bacillus phage phi 15 was active in formation of the phi 29 p3-dAMP complex, whereas the protein-DNA complex isolated from Bacillus phage GA-1 or from the pneumococcal phage Cp-1, both with a morphology similar to that of phage phi 29, as well as that obtained from adenovirus, were inactive.